Determinants of commercial bank interest rate spread in Malaysia / Jasmin Mohamed Ali - Mohamed Ali, Jasmin (2007)
The main objective of this paper is to study the determinant of bank interest spread in Malaysia. It uses a set of bank's characteristics which are the microeconomic variables and a set of macroeconomic variables to explain the bank interest spread. Macroeconomic variables included are the inflation rate and economic growth. For microeconomic variables, it consists of ratio of non-interest bearing deposit to total assets, net worth, operating costs, service revenue to total operational revenue, liquidity and leverage. This paper makes use of the annual data of 23 commercial banks in Malaysia which consists of 10 locally owned banks and 13 locally incorporated foreign banks. A period of six years which is from 2000 to 2005 is covered. A two step regression analysis is employed to measure the micro and macroeconomic variables. In consistent with previous research, it is found that macroeconomic variables are more relevant in explaining the bank's interest rate spread in Malaysia than microeconomic variables. Also, all the variables included are found to be significant in explaining the interest rate spread except for the variable of service revenue to total operational assets. It was also highlighted that operating costs is the main determinants of the interest rate spread.